1999
DOI: 10.1046/j.1439-0442.1999.00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cardiopulmonary Effects of Medetomidine–Midazolam, Acepromazine–Butorphanol and Midazolam–Butorphanol in Dogs

Abstract: Cardiopulmonary effects of intramuscualar administration of medetomidine-midazolam at 20 mg/kg and 0.3 mg/kg, respectively (MM), acepromazine-butorphanol at 0.05 and 0.2 mg/kg, respectively (AB), and midazolam-butorphanol at 0.1 and 0.2 mg/kg, respectively (MB), were compared in dogs. MM produced relatively large cardiovascular changes such as bradycardia, hypertension, a decrease in cardiac output and vasoconstriction. AB produced moderate cardiovascular changes. Hypotension was observed within 5 min after ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
1
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 9 publications
2
25
1
3
Order By: Relevance
“…In dogs, a similar decrease in BP has been observed during the first 20 min post-injection of a butorphanol-midazolam combination (Kojima et al, 1999), with intramuscular doses of 0.2 mg/kg each decreasing SAP by 15 mmHg (Novellas et al, 2007). Since we could not measure NIBP in unsedated ferrets, it was not possible to determine whether midazolam and butorphanol affected BP at the dosages used in our study.…”
Section: Discussionsupporting
confidence: 64%
“…In dogs, a similar decrease in BP has been observed during the first 20 min post-injection of a butorphanol-midazolam combination (Kojima et al, 1999), with intramuscular doses of 0.2 mg/kg each decreasing SAP by 15 mmHg (Novellas et al, 2007). Since we could not measure NIBP in unsedated ferrets, it was not possible to determine whether midazolam and butorphanol affected BP at the dosages used in our study.…”
Section: Discussionsupporting
confidence: 64%
“…The doses were determined based on previous research [5,8] and the drugs were administered 10 to 15 min before the induction of anesthesia. The specific combination of premedicants administered to each dog was chosen by the anesthetists according to the physical status of the animal.…”
mentioning
confidence: 99%
“…In the present study, bradycardia was observed in 27.5% of the MB group, 40% of the AB group and 70% of the Med group after the administration of premedicants or propofol. It has been reported that changes in heart rate after the administration of MB or AB are usually mild and that bradycardia observed in dogs premedicated with MB and AB may be induced by the additive or supra-additive effects of MB or AB and propofol [8]. It is also well known that medetomidine induces severe bradycardia in dogs [3,15].…”
mentioning
confidence: 99%
“…Administration of preanesthetic medications is also valuable for reducing the required dose of injectable anesthetics needed for induction of anesthesia and may result in fewer adverse effects or effects of lesser severity. [8][9][10][11][12][13] In other studies 14,15 conducted by our laboratory group, sedative and cardiopulmonary effects of 3 combinations of preanesthetic medications (medetomidinemidazolam [MM], acepromazine-butorphanol [AB], and midazolam-butorphanol [MB]) were evaluated in dogs. Administration of MM induces deep sedation accompanied by analgesia and muscle relaxation and also depresses arousal reactions to external stimuli.…”
mentioning
confidence: 99%